STUDIES ON THE CHEMICAL QUALITY OF CURED FISH PRODUCTS FROM THE WEST COAST OF INDIA
Fish curing is one of the oldest industries of the coastal areas of India. It has been estimated that about 50 to 70% of the marine fish catches of India are at present being processed into cured products Government of India Publication, 1951 a and b). Though fish curing is of this magnitude, it is one of the least developed industries of India, although efforts are being made in some of the maritime States such as Madras, Travancore-Cochin and Bombay, to improve curing by providing better facilities to the fishermen engaged in the industry. The methods practiced are generally primitive and the attention paid to cleanliness and sanitation leaves much to be desired. Only 17-3% of the total fish landing is being cured through the Government fish curing yards Government of India Marketing Report, 1951), the rest being processed in private yards which are not under the supervision of Government agencies., number=1, journal=Indian Journal of Fisheries, author=Krishna Pillai, V and Valsan, A P and Rajendranathan Nayar, M, year=2015, month=Feb.